48.7k views
0 votes
2x • 3x 2

Multiply or divide as indicated.

2 Answers

5 votes

Answer:
6x^3

Explanation:

You need to remember a property called "Product of powers property". This property states the following:


(a^m)(a^n)=a^((m+n))

In this case you can observe that the bases of the expression
2x*3x^2 are equal, this means that you can apply the property mentioned before.

Knowing this you can make the multiplication.

Then, the product you get is:


2x*3x^2=6x^((1+2))=6x^3

User Anil Kesariya
by
5.3k points
5 votes

For this case we have the following expression:


2x * 3x ^ 2 =

By definition of multiplication of powers of the same base, we have to put the same base and add the exponents, that is:


a ^ n * a ^ m = a ^ {n + m}

So:


2x * 3x ^ 2 = (2 * 3) x^(1 + 2) = 6x ^ 3

Answer:


6x ^ 3

User Ricardo Velhote
by
4.9k points